PENGARUH KOMUNIKASI PETUGAS LAPANGAN KB TERHADAP EFEKTIVITAS PROGRAM KB DI KOTA SUKABUMI - Nata Rinaldi Putri; Ike Rachmawati; Rizki Hegia Sampurna (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
The purpose of this study was to determine the effect of family planning field officer communication on the effectiveness of the family planning program in Sukabumi City. The method used in this research is descriptive method and associative method with a quantitative approach. The sampling technique in this study using purposive sampling. And in this case, that is 100 people who are registered in the family planning program. The data analysis technique used is a simple linear regression analysis technique, including the coefficient of determination test, simple correlation coefficient, and partial test (T test). The results of the study, using the coefficient of determination test, seen from the value (Adjusted R2) of 0.603, this means that the influence of family planning field officer communication on the effectiveness of family planning programs in Sukabumi is 60.3%, the remaining 39.7% is influenced by other factors that are not explained. in this research. From the results of the correlation coefficient test, it can be seen that the R value is 0.776, indicating a strong relationship between communication with family planning field officers and the effectiveness of the family planning program.